2018
DOI: 10.1016/j.celrep.2017.12.082
|View full text |Cite
|
Sign up to set email alerts
|

A Long Cytoplasmic Loop Governs the Sensitivity of the Anti-viral Host Protein SERINC5 to HIV-1 Nef

Abstract: SUMMARY We recently identified the multipass transmembrane protein SERINC5 as an antiviral protein that can potently inhibit HIV-1 infectivity and is counteracted by HIV-1 Nef. We now report that the anti-HIV-1 activity, but not the sensitivity to Nef, is conserved among vertebrate SERINC5 proteins. However, a Nef-resistant SERINC5 became Nef sensitive when its intracellular loop 4 (ICL4) was replaced by that of Nef-sensitive human SERINC5. Conversely, human SERINC5 became resistant to Nef when its ICL4 was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 33 publications
4
56
0
Order By: Relevance
“…Because these viral antagonists of the Serinc proteins presumably function by affecting membrane trafficking, whether the presence or absence of an intact PSAC motif in Serinc proteins affects their activity remains an interesting and open question. So far, we have shown only that the presence or absence of an intact PSAC has no influence on the activity of a single HIV-1 Nef protein as an antagonist of Serinc3, even though the analogous cytoplasmic loop has recently been shown to be a determinant of the susceptibility of Serinc5 to Nef proteins (36).…”
Section: Discussionmentioning
confidence: 90%
“…Because these viral antagonists of the Serinc proteins presumably function by affecting membrane trafficking, whether the presence or absence of an intact PSAC motif in Serinc proteins affects their activity remains an interesting and open question. So far, we have shown only that the presence or absence of an intact PSAC has no influence on the activity of a single HIV-1 Nef protein as an antagonist of Serinc3, even though the analogous cytoplasmic loop has recently been shown to be a determinant of the susceptibility of Serinc5 to Nef proteins (36).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to other antiviral restriction factors, SERINC5 is highly conserved and orthologs from various vertebrate species display antiretroviral activity [ 10 ]. Recently, however, it has been shown that frog SERINC5 is resistant to HIV-1 Nef and further demonstrated that the sensitivity is governed by the intracellular loop 4 (ICL4) of the restriction factor [ 39 ]. We confirmed these previous findings for HIV-1 NL4-3 Nef, as well as the finding that SIVmac239 Nef is broadly active and capable of counteracting frog SERINC5 ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pBJ6 vector expressing HA-tagged SERINC5, pBJ5 vector expressing HA-tagged MLV glycoGag as well as the pSERINC-GFP vectors have been previously reported [ 8 ]. Human SERINC5 mutants L350A and I352A, as well as frog and zebrafish orthologs and frog/human SERINC5 chimeras were described before [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Full-length SERINC5 cDNA sequences were amplified from RNA extracted from human and rhesus macaque PBMCs by RT-PCR and cloned into the Not I and Bam HI sites of pQCXIH. Sequences encoding an HA epitope tag were introduced into an extracellular loop of SERINC5 between residues 290 and 291 as previously described [57]. Plasmid DNA constructs for the expression of firefly luciferase from a promoter with three NF-κB binding sites and Gaussia luciferase were provided by Dr. Daniel Sauter (Ulm University Medical Center, Ulm, Germany) [41].…”
Section: Plasmid Dna Constructsmentioning
confidence: 99%